2011
DOI: 10.4028/www.scientific.net/amr.325.693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hard Materials Using Eco-Attributes

Abstract: Hard materials based on Alumina (AN), Silicon Carbide (SC), Boron Carbide/Nitride (BC/N), Zirconia (ZN), and alike are often used to produce abrasive grains and coat cutting tools. These materials improve the performance of grinding/machining operations by providing an enhanced productivity, a longer grinder/tool life, and a better surface finish. On the other hand, they might leave some burdens on the environment. Therefore, eco-attributes (i.e., energy consumption, CO2 emission, NOX/SOX emission, water usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As mentioned before, the shape of the abrasive grains are highly stochastic in nature [3][4] creating uneven heights of the cutting edges located on the outermost circumferential surface of a grinding wheel. The same argument holds for the wear/truncation of the abrasive grains (e.g., see the work [14] where the authors have reported the experimental results showing the randomness in the wear of the materials (cBN and diamond) used to produce the abrasive grains [1][2]). As a result, one can use the abrasive grains' wear, truncation, loss, and shape-relevant stochastic information to create the uneven heights of the grains.…”
Section: Issues Of Surface Generation Mechanism Of Grindingmentioning
confidence: 65%
See 1 more Smart Citation
“…As mentioned before, the shape of the abrasive grains are highly stochastic in nature [3][4] creating uneven heights of the cutting edges located on the outermost circumferential surface of a grinding wheel. The same argument holds for the wear/truncation of the abrasive grains (e.g., see the work [14] where the authors have reported the experimental results showing the randomness in the wear of the materials (cBN and diamond) used to produce the abrasive grains [1][2]). As a result, one can use the abrasive grains' wear, truncation, loss, and shape-relevant stochastic information to create the uneven heights of the grains.…”
Section: Issues Of Surface Generation Mechanism Of Grindingmentioning
confidence: 65%
“…Grinding is a complex material removal process [1] where a grinding wheel gradually removes materials from the work-surface. Abrasive grains (made of very hard materials [2]) are bonded to form a grinding wheel [1]. The microscopic structures of the outermost circumferential surface of a grinding wheel, as well as the shape of the abrasive grains, are highly complex [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…GHG emissions associated with direct energy consumption were estimated using an emission factor of 0.0653 t/MWh, whose value is based on the Brazilian electricity mix for the base year of 2012 and obtained from the Ministry of Science, Technology, and Innova tion database. GHG emissions associated with indirect energy consumption were estimated using emission factors of 1.54 t/t for steel [39] and 9 t/t for tungsten carbide, based on another material with a similar processing route [40]. Particulate material emissions were disregarded in this study.…”
Section: Environmental Indicators Based On a Streamlined Life Cycle Assessment (Lca) Frameworkmentioning
confidence: 99%